PENDAMPINGAN KELAS IBU HAMIL MELALUI LAYANAN BIMBINGAN DAN KONSELING ISLAM UNTUK MENGURANGI KECEMASAN PROSES PERSALINAN - Mintarsih, Widayat (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2017)
Physical and psychological changes cause problems for pregnant women such as: lack of confidence, dependence on partner, even worried and anxious. To reduce the anxiety, women need assistance through the process of Islamic guidance and counseling services. It is an effort to help individual overcome such deviations of religious nature as well as accept his role as khalifah that create good relationship with God, man and the universe. The lack of Islamic guidance and counseling services provided by health workers from hospital or village midwives brings the enthusiasm to get Islamic counseling especially for pregnant women, their families, integrated services post (Posyandu) cadres, and society in general to be able to overcome their problems. Method of PAR (Participatory Action Research) through awarenes actions towards their condition was used in this research. Assistance through Islamic counseling services meets the needs of pregnant women to reduce anxiety in order to maintain physiological, psychological, and spiritual health. In addition, this kind of services gives an increasing knowledge and insight cognitively, affectively, and psychoÂmotor for pregnant women. Internal cares both medically and through Islamic guidance and counseling services to reduce anxiety for pregnant women is done by themselves, their husband and family while external assistance can be done by the cadres of integrated services post, midwives, and community leaders. An increase and decrease in anxiety were measured by Hamilton Rating Scale for Anxietyâs theory (HRS-A) in Hawari. The result analysis showed that there were 11 clients experiencing decreased anxiety after receiving the Islamic counseling services. Before services, it was found a person suffering from slight category of anxiety, in which indicated the range of 14-20. Moreover, it was found 10 people suffering from medium category of anxiety, with total criteria of assessment from range 21-27._________________________________________________________Perubahan fisik dan psikologis menyebabkan problematika bagi ibu hamil, seperti kurang percaya diri, ketergantungan kepada pasangan, bahkan sampai merasa khawatir dan cemas Untuk mengurangi kecemasan dibutuhkan pendampingan melalui proÂses layanan bimbingan dan konseling Islam. Minimnya layanÂan bimbingan dan konseling Islam yang diberikan oleh petugas keÂsehatan dari Puskesmas atau bidan desa menyebabÂkan antusias warga khususnya ibu hamil menginginkan diadakannya layanan bimbingan dan konseling Islam khususnya ibu hamil, keluarga ibu hamil, kader Posyandu, dan masyarakat pada umumnya agar mampu mengatasi masalah yang mereka alami. Metode PengÂabdian yang dilakukan berbasis PAR (Participatory Action Research) melalui penyadaran tindakan menuju perbaikan konÂdisi kehidupan mereka. Pendampingan melalui layanan bimÂbingan dan konseling Islam memenuhi kebutuhan ibu hamil untuk mengurangi kecemasan sehingga bisa menjaga keÂsehatan fisiologis, psikologis, dan spiritual, serta ada peÂningkatÂan peÂngeÂtahuan dan wawasan dari segi kognitif, afektif, dan psikoÂmotorik. Pendampingan secara medis dan melalui layanan bimÂbingan dan konseling Islam untuk mengurangi keÂcemasan interÂnal ibu hamil dilakukan oleh diri sendiri, suami, dan keluarga sedangkan pendampingan eksternal bisa dilakukan oleh kader Posyandu, para bidan, dan tokoh masyarakat. PeÂningkatan dan penurunan kecemasan didiagnosa menggunaÂkan alat ukur teori Hamilton Rating Scale for Anxiety (HRS-A) dalam Hawari yang menghasilkan analisis bahwa terdapat 11 klien yang mendapatÂkan layanan bimbingan dan konseling Islam mengÂalami peÂnurunan kecemasan. Sebelum mendapatkan layaÂnÂan, terÂdapat 1 orang mengalami kecemasan kategori ringan dengan kriteria total penilaian dari rentang 14-20 dan kategori keÂcemasan sedang ada 10 orang dengan kriteria total penilaian dari rentang 21-27.